The Influence Of Promotion And Brand Image On Purchasing Decisions For Al Amin Skin Care Products In Tasikmalaya City (Survey Of Al Amin Skin Care Customers In Tasikmalaya City): - Aliyah, Siti Arum Himmatun; Karmila, Mila; Wibawa, Gian Riksa (CV. Utami, 2024)
The purpose of this study is to determine the simultaneous and partial influence of the Promotion variable and Brand Image variable on Purchasing Decisions. The method used in this research is causality through a survey approach. With a research sample of 100 Al Amin Skin Care Customers in Tasikmalaya City. The data used is primary data and secondary data. The analysis tool used in this study is multiple linear regression using SPSS 26.0. The results of the study show that Promotion and Brand Image have a significant effect on Purchasing Decisions for Al Amin Skin Care Products in Tasikmalaya City. Partially, promotion does not have a significant influence on purchasing decisions for Al Amin Skin Care products in Tasikmalaya City. Partially, Brand Image has a significant influence on Purchasing Decisions on Al Amin Skin Care Products in Tasikmalaya City.